The poverty reduction role of rural development centres: a case study of Gibeon Constituency, Namibia - Hatutale, Gabriel Kamanya (University of the Free State, 2020)
The study explored the role of rural development centres in rural poverty reduction in the Gibeon Constituency in the Hardap region in Namibia. A qualitative research approach was utilised, using semi-structured interviews and in-depth interviews using a questionnaire as an instrument to collect data. The purposive sampling technique was used to select a sample to participate in the study. The research participants were selected based on the consideration that they can give rich information and able to share their understanding of what and how they feel and see rural poverty, what causes it in their own views and perceptions, and what rural poverty means to them. The study findings have shown that the community in the Gibeon Constituency, mostly the rural inhabitants, are in fact poor due to lack of social services (education, health care, housing and transportation), poor service delivery, limited services, insecurity of land tenure, overcrowding in the communal land, limited opportunity for farming, vastness and remoteness in terms of service delivery. Rural poverty is on the increase, irrespective of the Namibian social services (education, health care, housing and public transportation) being subsidised. About two thirds of the Namibian population are found in the rural areas in a situation where they are excluded from the provision of social and economic needs which are being delivered by the government. The limited access to service provision such as access to better road networks, electricity, water, housing, rural markets, banking, credit facilities, as well as the limited access to low level of agricultural technology and the slow pace of the decentralisation process, remain a challenge to rural development. There is high level of unemployment in the Gibeon Constituency. The study recommends that the Gibeon Constituency, through the regional government (Hardap Regional Council) should speed up the process of service delivery by decentralising the key ministries dealing with poverty and social well-being of the community. Both the oldage grant and children’s grant should be increased and the pro-poor policies should take into account local and regional factors when designing interventions to address poverty in line with the sustainable development principle of subsidiarity.
Dissertation (MDS (Development Studies))--University of the Free State, 2020
Keywords: Rural development centre; Rural poverty reduction; Social protection; Social services; Livelihood; Rural markets; Desirable services; Itemize services; Extension services; Access to land; Poverty reduction